Effect of V Dopant on Physicochemical Properties of Vanadium-Doped Anatase Synthesized via Simple Reflux Technique - Sutrisno, Hari; Ariswan, Ariswan; Purwaningsih, Dyah (Journal of Mathematical and Fundamental Sciences, 2016)
Mesoporous pure TiO2 (M-TiO2) and mesoporous-vanadium-doped TiO2 (M-V-doped TiO2) were successfully synthesized via a facile and simple reflux technique. The purpose of this research was to study the effect of vanadium dopant on the physicochemical properties of all materials obtained. Characterization of the prepared materials was carried out using X-ray diffraction (XRD), scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) and N2-adsorption-desorption analysis. The presence of Ti and O elements in M-TiO2 and of Ti, V and O elements in M-V doped TiO2 could be detected by SEM-EDS, while the patterns of X-ray diffraction of all the prepared samples had a well-crystalline surface of anatase type. All mesoporous vanadium-doped TiO2 (M-V-doped TiO2) materials performed in a highly transparent mode in the visible region at 554 nm (Eg = 2.24 eV) and 588 nm (Eg = 2.12 eV) for 3.3 and 4.9 wt% V doped TiO2, respectively. The Rietveld refinement method was applied to extract the structural parameters of the M-TiO2 and M-V-doped TiO2 using the Fullprof program in the WinPlotr package. The prepared materials were refined in the crystal system and space group of anatase (tetragonal, I41/amd (141)). The vanadium ion was successfully doped into TiO2. The isotherm type of M-TiO2 and 2.3 wt% V doped TiO2 were of type IV, with a profile of type H2 hysteresis loops, while the 3.3 and 4.9 wt% vanadium-doped TiO2 reflected isotherm type III. The Brunauer-Emmett-Teller (BET) results showed a significant reduction in surface area due to increased concentrations of vanadium. The highest values of BET-specific surface area, pore volume and average pore size of M-TiO2 were 46 m2/g, 18.45 nm and 0.2572 cm3/g respectively.